HOW ENTREPRENEURIALLY INFLUENTIAL SOCIAL TRAITS AFFECT BUSINESS CREATION AMONGST RURAL IMMIGRANTS: Evidence from Spain - Claudio Mancilla; Yancy Vaillant; Esteban Lafuente (European Regional Science Association (ERSA), 2010)
Usually, immigrants have been studied as employed work force. However, they often choose to become entrepreneurs. According to the relevant literature, there are evidences that immigrants are more entrepreneurially active than local inhabitants. However, results from the Global Entrepreneurship Monitor for Spain show that this is not consistent across the urban-rural divide. Explanation for variances in entrepreneurship in rural as compared to urban areas have been linked to specific socio-institutional traits that exert a differentiated impact on the entrepreneurial activity levels of specific segments of the population. The objective of this study is to verify how the entrepreneurial activity of rural immigrants responds to socio-institutional traits that have been identified as key explanatory factors of entrepreneurial behaviour. To carry out this research, the Spanish Global Entrepreneur Monitor (GEM) data set from 2008 was used. We conduct a comparative analysis between three population groups: immigrants as compared to non-immigrant, rural immigrant as compared to urban immigrant, and rural immigrants as compared to rural non-immigrants. To do this, a rare events logit regression model was applied. The results indicate that the probability to become an entrepreneur is greater for immigrants. The same is true for an individual residing in a rural area. However, contrary to Spaniards, rural immigrants are not more likely to become entrepreneurs. We find explanation for this in the econometric analysis of the selected socio-institutional traits.
Keywords: M13; O18; 330; Immigrants; Entrepreneurship; Rural areas; Concentration of immigrants